Factors that influence house purchase intention in Johor Bahru by SSI Properties Sdn Bhd / Nor Amira Mohd Jamal - Mohd Jamal, Nor Amira (2018)
Nowadays,' property has becomes the most basic need for human life. Property is something that can ensure your life in future more better because the purchase of property never will make' someone loss. As we notices, there are more developers in this challenging economy market conditions. They are very competitive to each other in order to sell their property by giving different kind of promotion, rebates and other than that. The purpose of this study was to determine factors that influence house purchase intention among consumer in Johor Bahru. The data for this study was collected using a survey of questionnaire. Customers who purchase the property with SSI- Propel-ties Sdn Bhd would be the target population. A sample of 100 questionnaires was distributed to the respondent who have intention to purchase a property in Johor Bahru. The Statistical Package for Social Sciences (SPSS) version 22.0 was used to analyze the data collected through the survey. A few recommendations are presented to propose beneficial suggestions for future used.